THE STATUS OF FRENCH LOANWORDS IN THE INDONESIAN LANGUAGE - Hayatul Cholsy; I Dewa Putu Wijana; F.X Nadar; Wening Udasmoro (Humaniora, 2014)
The inclusion of French loanwords in the Indonesian language cannot be separated from the fact that there have been contacts between the two languages. In the process the French words underwent interference due to the different systems between the Indonesian Language and French, such as phonetic and ortographic system, in addition to the different structure of word formation of both languages. This phenomenon is closely linked to the status of French loanwords in the Indonesian language, whether they are interference or already integrated with the Indonesian language. In light of this, this study aims to examine whether French loanwords in the Indonesian Language are in the state of interference or already have integration status. This Study shows that the majority of French loanwords in Indonesian are still in the forms of interference. This is because these loanwords are still in their original forms – French words. Other French loanwords are already integrated with the Indonesian language, especially those having undergone consistent adjustments through their spoken and written use.